Pleiotropic effects of Erythropoietin. Influence of Erythropoietin on processes of mesenchymal stem cells differentiation - Ekaterina V. Zubareva; Sergey V. Nadezhdin; Yuriy E. Burda; Natalia A. Nadezhdina; Anastasia S. Gashevskaya (Belgorod National Research University, 2019)
Structure and synthesis of Erythropoietin: Erythropoietin (EPO) is a glycoprotein hormone. Recombinant Erythropoietin (Epoetin): Human recombinant erythropoietin is characterised as a factor which stimulates differentiation and proliferation of erythroid precursor cells, and as a tissue protective factor. Anti-ischemic effects of recombinant Erythropoietin: Erythropoietin is one of the most perspective humoral agents which are involved in the preconditioning phenomenon. Erythropoietin receptors and signal transduction pathways: Erythropoietin effects on cells through their interconnection with erythropoietin receptors, which triggers complex intracellular signal cascades, such as JAK2/STAT signaling pathway, phosphatidylinositol 3-kinase (PI3K), protein kinase C, mitogen-activated protein kinase (MAPK), and nuclear factor (NF)-κB signaling pathways. Mechanisms of the effect of Erythropoietin on hematopoietic and non-hematopoietic cells and tissues: In addition to regulation of haemopoiesis, erythropoietin mediates bone formation as it has an effect on hematopoietic stem cells and osteoblastic niche, and this illustrates connection between the processes of haematopoiesis and osteopoiesis which take place in the red bone marrow. The effect of Erythropoietin on mesenchymal stem cells and process of bone tissue formation: Erythropoietin promotes mesenchymal stem cells proliferation, migration and differentiation in osteogenic direction. The evidence of which is expression of bone phenotype by cells under the influence of EPO, including activation of bone specific transcription factors Runx2, osteocalcin and bone sialoprotein. Conclusion: Erythropoietin has a pleiotropic effect on various types of cells and tissues. But the mechanisms which are involved in the process of bone tissue restoration via erythropoietin are still poorly understood.